Case Study : Myr Construction Sdn.Bhd. / Nur Baizura Abdullah - Abdullah, Nur Baizura (2020)
MYR Construction SDN BHD is a company incorporated on 20 October 1994 under Company Act 1965 and is located in Kota Bharu , Kelantan. The firm has been operating for 26 years and is a well-established business. The company's goal is to become a prosperous local enterprise in the furniture industry. Service that were provided by the company is dealing, designing and creating office furniture for the government and private sector , developer of furniture for educational institution and creating and designing cabinet and furniture for houses. The problems that were faced by the company is unorganised leftover chipboard and time consuming of the design to the machine. The idea to overcome the problem should focused more on how to recycle the waste product which can benefit for the company instead of throwing all those high quality products and create a program that will direcltly link the computer office to the machines